Short Communication: Silba adipata (Diptera: Lonchaeidae) parasitoids on cayenne pepper (Capsicum frutescens) in Bali, Indonesia - Ketut Ayu Yuliadhi; I WAYAN SUPARTHA; NI NENGAH DARMIATI; ALPREDO BANGUN; I KADEK WISMA YUDHA; I WAYAN EKA KARYA UTAMA; PUTU ANGGA WIRADANA (Society for Indonesian Biodiversity, 2021)
Abstract. Yuliadhi KA, Supartha IW, Darmiati NN, Bangun A, Yudha IKW, Utama IWEK, Wiradana PA. 2021. Silba adipata (Diptera: Lonchaeidae) parasitoids on cayenne pepper (Capsicum frutescens) in Bali, Indonesia. Biodiversitas 22: 3929-3935. The black fig fly (Silba adipata) is newly emerging pests that attack cayenne pepper (Capsicum frutescens L.) plants in Bali Province, Indonesia. This study aimed to determine the parasitoid type, community structure, distribution, and parasitization rate of the parasitoids of S. adipata on cayenne pepper in Bali. The sampling method employed in this study involves purposive sampling techniques on 100-150 pieces of cayenne pepper infested with S. adipata at each location point, with the emerging parasitoids identified morphologically. Three types of parasitoid species were associated with S. adipata, which include Asobara japonica Belokobylskij, Fopius arisanus (Sonan), and Diachasmimorpha longicaudata (Ashmead). The parasitoid community structure associated with S. adipata had a low abundance index, low diversity index, and a moderate dominance index. Based on the distribution of the three parasitoids, D. longicaudata is distributed evenly in Bali, whereas F. arisanus was not found in Jembrana . Conversely, A. japonica was only found in Badung, Bangli, Gianyar, and Klungkung. As summary, D. laungicaudata had the highest parasitization rate compared to the F. arisanus and A. japonica. D. longicaudata is a potential parasitoid, which can be studied for the future biological control of S. adipata.